2010
DOI: 10.1002/hep.23915
|View full text |Cite
|
Sign up to set email alerts
|

miR-194 is a marker of hepatic epithelial cells and suppresses metastasis of liver cancer cells in mice

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression by interacting with the 3′ untranslated region (3′-UTR) of multiple mRNAs. Recent studies have linked miRNAs to the development of cancer metastasis. In this study, we show that miR-194 is specifically expressed in the human gastrointestinal tract and kidney. Moreover, miR-194 is highly expressed in hepatic epithelial cells, but not in Kupffer cells or hepatic stellate cells, two types of mesenchymal cells in the liver. miR-194 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
168
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 51 publications
(53 reference statements)
10
168
0
1
Order By: Relevance
“…In addition, in cancer of the gut (37,38) and kidney (39), miR-194 served a similar inhibitory role. By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, in cancer of the gut (37,38) and kidney (39), miR-194 served a similar inhibitory role. By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40).…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40). These studies indicated that miR-194 had various target genes (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Previous studies have demonstrated that miR-194 inhibited cell migration and invasion, which may have contributed to the anti-tumor activity of trastuzumab on HER2-overexpressing breast cancer cells (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Jin et al (23) overexpression of miR-194 in highly metastatic pancreatic ductal adenocarcinoma, and overexpression of miR-215 in hepatocellular carcinoma by microarray and real-time PCR methods (7-9). However, miR-194 in mouse hepatocellular carcinoma and cancer cell lines was downregulated by the real-time PCR method (24). Therefore, the altered miRNA expression levels may cause tissue-specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…The livers were prepared as either paraffin sections or frozen section as described previously. 13,14 The sections were stained with hematotxylin and eosin (H&E) or in situ cell death kit (Roche Applied Science, Indianapolis, IN, USA). To quantify the number of cell deaths, six fields were randomly chosen from each liver section.…”
Section: Stainingmentioning
confidence: 99%